Assessing energy flexibility: a comparative review of Nigeria and the United Kingdom - Akporhonor, Gbubemi Kevin; Mirzania, Pegah (Springer, 2025)
This paper provides a comparative analysis of the energy systems in Nigeria and the United Kingdom (UK), focusing on market instruments for energy flexibility to achieve NetZero emissions under the Paris Agreement. Through a systematic review using Scopus database, the study identifies key energy flexibility instruments in Nigeria, including energy efficiency initiatives, smart metering, peer-to-peer energy trading, decentralised energy systems, and independent power plants. Supporting policies include Renewable Energy Master Plan, National Energy Efficiency Action Plan, and National Renewable Energy Action Plan. However, Nigeria faces challenges like low electrification rates, underutilised grid capacity, and fragile infrastructure, resulting in power outages. Conversely, the UK’s energy system features advanced Demand-Side Response Programmes, Smart Grid Technologies, Energy Storage Solutions, and Virtual Power Plants, supported by policies and initiatives like Agile Octopus Smart Meters. Learning from the UK’s successes evidenced by its high ranking on the World Energy Council Energy Trilemma Index, this study recommends that Nigeria improve its power infrastructure and incorporate energy flexibility instruments. By expanding power capacity, upgrading the grid, enhancing flexibility mechanisms, creating roadmaps, and transparent allocation and use of financial resources. These actions are essential for enhancing the reliability and sustainability of Nigeria’s energy system to achieve a Just Transition.
Keywords: 4802 Environmental and Resources Law; 46 Information and Computing Sciences; 48 Law and Legal Studies; 7 Affordable and Clean Energy; 13 Climate Action